Implementasi Akuntansi untuk Mengukur Dampak Lingkungan dalam Pelaporan Keberlanjutan - Marsono; Dewayanto, Totok (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study explores the implementation of accounting practices in measuring and reporting environmental impacts within sustainability reporting frameworks. Using a qualitative approach through comprehensive literature review and library research methodology, this research analyzes the current practices, challenges, and effectiveness of environmental accounting in corporate sustainability reporting. The study examines data from academic publications, scientific journals, and relevant research papers to understand how organizations integrate environmental costs and impacts into their accounting systems. The findings reveal that companies implementing established sustainability accounting frameworks demonstrate a 25% improvement in environmental performance and a 30% increase in transparency. The research also identifies several key challenges, including the lack of standardized reporting guidelines and insufficient integration of environmental costs into financial decision-making processes. Furthermore, the study highlights that firms with higher environmental performance, larger size, and lower debt ratios show improved productivity in their sustainability reporting practices. The implementation of environmental accounting not only enhances corporate accountability but also contributes to better decision-making processes and environmental stewardship. This research contributes to the existing literature by providing insights into effective environmental impact measurement methodologies and suggesting practical approaches for improving sustainability reporting practices.